Farmer fertilization practices of mature rubber plantations in Northeast Thailand during a period of low rubber prices - Supattra Kullawong; Satit Aditto; Bénédicte Chambon; Arunee Promkhambut (Forestry Faculty, Universitas Hasanuddin, 2020)
Since 2000, farmers in Northeast Thailand have planted more than 5,000 sq km of rubber on land previously devoted to agriculture. The expansion of rubber led to a significant increase in tree cover in Northeast Thailand. Rubber prices peaked in 2011 and since then farmers have had to adjust to lower prices. Little research has documented how farmers responded to low rubber prices. This paper seeks to describe how small-scale rubber farmers use fertilizer in a region that did not historically grow rubber during a period of low rubber prices. We collected data from structured interviews with 29 farmers in Subsomboon village in Khon Kaen province, Northeast Thailand. Most farmers reported that they reduced fertilizer costs by reducing the number of times they applied fertilizer, as well as changing to cheaper brands and/or using organic fertilizer. The majority of farmers still used large amounts of chemical fertilizers, either alone or in combination with commercial organic fertilizers with unknown nutrient contents. The N and P2O5 contents of the chemical fertilizer alone were consistent with national recommendations (82.0–137.6 kg N/ha/y and 33.3–97.7 kg P2O5/ha/y). Thai national recommendations for rubber, however, were developed for rubber plantations in traditional planting areas where rubber has been grown for over a century, and are considered by many experts to be high. The study’s findings indicated that small scale rubber farmers would benefit from recommendations for fertilizer applications that respond to variations in rubber prices, while taking into account the diversity of individual household characteristics and goals. To optimize recommendations that sustain the growth and yield of rubber, limit the effects of environmental externalities, and maintain rubber’s profitability, policymakers require detailed information on the diverse situations in which rubber is grown. This requires experimental research that tests a variety of fertilization practices under different biological and physical conditions.